Auxiliary Verb And Action Verb In Educational News Articles Of Bbc. Com In 2024 - Irene Adryani Nababan; Anita Sitanggang; Rohanna Sinambela (CV Putra Publisher, 2026)
An online newspaper is a digital version of a traditional print newspaper, accessible through the internet. It offers news, features, editorials, and various articles covering current events, politics, sports, entertainment, and other topics. Online newspaper, especially daily newspaper, has a big contribution to the people. People can get information about local or international events every day because the news and information are up-to-date and accurate. This research aims to find out the use and the classification of auxiliary verbs and action verbs found in educational news article of BBC.com in 2024 and students perspective in auxiliary verbs and action verbs found in educational news article of BBC.com in 2024. The researcher will use the descriptive design, a research design that aims to describe and interpret things in line with reality. The data in this research will be analyzed in the form of word description and identification or analysis of the types of auxiliary verbs and action verbs in educational news article of BBC.com in October 2024. Twenty questionnaires will be given to all the students and ten questions to ten students in interview section to answer the students perspective in auxiliary verbs and action verbs found in educational news article of BBC.com on 2024. Also, the researchers suggest for teacher to use online media such as online newspaper in the learning process and for students always to increase their motivation to read the online newspaper to learn English grammar especially auxiliary verb and action verbs. This research will be published in Sinta 4 journal.